Carboxylesterase-2-Selective Two-Photon Ratiometric Probe Reveals Decreased Carboxylesterase-2 Activity in Breast Cancer Cells - Park, Sang Jun; Kim, Yun Ji; Kang, Ji Su; Kim, In Young; Choi, Kyeong Sook; Kim, Hwan Myung (Analytical Chemistry, 2018)
Human carboxylesterase-2 (CE2) is a carboxylesterase that catalyzes the hydrolysis of endogenous and exogenous substrates. Abnormal CE2 levels are associated with various cancers, and CE2 is a key mediator of anticancer prodrugs, including irinotecan. Here, we developed a two-photon ratiometric probe for detecting CE2 activity using succinate ester as a recognition site for CE2. The probe showed high selectivity to CE2, a clear emission color change, high photostability, and bright two-photon microscopy (TPM) imaging capability, allowing the quantitative detection of CE2 activity in live cells. Using TPM ratio analysis, we show for the first time that CE2 activity was much lower in breast cancer cells than in normal cells. In CE2 overexpression studies, cancer cells had a markedly enhanced sensitivity to the cytotoxic effect of irinotecan, corresponding well with the TPM ratio of the probe. These results may provide useful information for quantitatively measuring CE2 activity in situ and predicting the responsiveness to anticancer drugs.
Keywords: Breast cancer cells; Carboxylesterases; Cytotoxic effects; Enhanced sensitivity; Exogenous substrates; Imaging capabilities; Quantitative detection; Two photon microscopy; Breast Neoplasms; Carboxylesterase; Cell Line, Tumor; Esterification; Female; Fluorescent Dyes; Humans; MCF-7 Cells; Microscopy, Fluorescence, Multiphoton; Optical Imaging; Photons; Succinic Acid